A probable skeleton of Isisfordia (Crocodyliformes) and additional crocodyliform remains from the Griman Creek Formation (Cenomanian, New South Wales, Australia). (March 2021) - Hart, Lachlan J.; Bell, Phil R.; Smith, Elizabeth T.; Mitchell, D. Rex; Brougham, Tom; Salisbury, Steven W.
Abstract: The sparse record of Cretaceous crocodyliforms in Australia comprises only three species, all within the genus Isisfordia. Isisfordia duncani Salisbury et al., 2006 is from the Albian–Turonian Winton Formation of Queensland, and both Isisfordia molnari Hart et al., 2019 and Isisfordia selaslophensis Etheridge, 1917 have been described from opalized material from the Cenomanian Griman Creek Formation of New South Wales. Here, we describe new cranial and postcranial material, including the most complete crocodyliform skeleton from the Cretaceous of New South Wales, which is assigned to Isisfordia cf. I. selaslophensis . We also reappraise previously described crocodyliform material from the same locality. We find that much of this material displays features that are consistent with Isisfordia .